Distribution and contamination assessment of selected heavy metals and rare earth elements in soil of Penang Island, Malaysia / Fatimah Az Zahra’ Abdul Hamid - Fatimah Az Zahra’, Abdul Hamid (2018)
This study focused on the distribution and contamination assessment of selected heavy metals and rare earth elements (REE) in top soil of Penang Island. Four heavy metals (As, Pb, Cd and Ni) and seven REE (La, Ce, Nd, Eu, Tb, Dy and Er) have been analysed in 31 soil samples using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The descending order of highest mean concentration of these elements was Pb > As > Ce > La > Nd > Ni > Dy > Er > Tb > Cd > Eu. Results of heavy metal concentrations showed that As content ranged from 67.9 to 2942.1 mg/Kg with mean value of 366.6 mg/Kg, Pb content ranged from 42.1 to 7019.6 mg/Kg with mean value of 422.9 mg/Kg, Ni content ranged from 6.5 mg/Kg to 1049.2 mg/Kg with mean value of 51.7 mg/Kg and Cd content ranged from 0.2 to 16.7 mg/Kg with mean value of 1.6 mg/Kg. REE concentration results showed that La content ranged from 34.0 to 218.9 mg/Kg with mean value of 82.1 mg/Kg, Ce content ranged from 70.1 to 602.3 mg/Kg with mean value of 191.2 mg/Kg, Nd content ranged from 28.8 to 201.9 mg/Kg with mean value of 72.9 mg/Kg, Eu content ranged from 0.14 to 5.86 mg/Kg with mean value of 1.16 mg/Kg, Tb content ranged from 0.77 to 6.23 mg/Kg with mean value of 2.01 mg/Kg, Dy content ranged from 3.12 to 24.20 mg/Kg with mean value of 8.57 mg/Kg and Er content ranged from 0.99 to 12.63 mg/Kg with mean value of 4.16 mg/Kg. In spatial distribution analysis, George Town, Batu Ferringhi, Jelutong and Bandar Air Itam were identified as high concentration areas of heavy metals whereas Teluk Bahang, Bandar Air Itam, George Town and Balik Pulau were identified as high concentration areas of REE. In contamination level assessment, Bandar Air Itam, George Town, Batu Ferringhi, Jelutong, Teluk Bahang, Tanjung Bunga and Balik Pulau were determined as high CF, Igeo and CI value of heavy metals and REE. The result of statistical analysis represented that the relationship among heavy metals was showed by Pb and Cd whereas the relationships among REE were represented by division of LREE and HREE. Between heavy metals and REE, the relationships were represented by As with Eu and Tb. The relationships between heavy metals and REE with soil physicochemical properties were represented by Cd and OM with positive correlation and, Nd and OM with negative correlation.